Finding internal and situational differences between two knowledge bases - Paliulionienė , Laima (Lietuvos matematikos rinkinys, 2004)
The task of comparing knowledge bases can emerge in different domains. It is sometimes essential to compare knowledge bases created by different experts for the same goal, or different versions of a knowledge base after amendments. The article presents a method of the automated comparing of knowledge bases, and offers an approach to its implementation. The method uses forward inference and model generating. Jess, the expert system shell for the Java platform, is proposed as an experiment basis, and constructs of F-logic are modelled by Jess.